2014
DOI: 10.1108/gm-05-2013-0049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a career development and mentoring programme on female mental health nurses

Abstract: Purpose – Literature has shown that mentoring and career development programmes can assist women and minority groups in pursuit of more senior roles. The Challenging Perceptions 12-month, multi-faceted career development and mentoring programme was specifically designed to aid female mental health participants in their attempts to break the glass ceiling, which can be apparent within senior levels of the UK National Health Service. This study aimed to investigate the effects of a career develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Within mentoring research, two predominant mentoring styles emerge: formal mentoring and informal mentoring. Formal mentoring is defined by structured relationships (Vatan & Temel, 2016); this type of mentoring has been found effective in addressing issues of gender and ethnic diversity (Woolnough & Fielden, 2014). Programs such as the Research (Bratt, 2009), the Challenging Perceptions nursing program in the United Kingdom (Woolnough & Fielden, 2014), and the Flying Start program for nurses within the National Health Service (NHS) in the United Kingdom (Solowiej, Upton, & Upton, 2010), all serve as formal mentoring programs that target the specific needs of those individuals within the profession.…”
Section: Types Of Mentoringmentioning
confidence: 99%
See 4 more Smart Citations
“…Within mentoring research, two predominant mentoring styles emerge: formal mentoring and informal mentoring. Formal mentoring is defined by structured relationships (Vatan & Temel, 2016); this type of mentoring has been found effective in addressing issues of gender and ethnic diversity (Woolnough & Fielden, 2014). Programs such as the Research (Bratt, 2009), the Challenging Perceptions nursing program in the United Kingdom (Woolnough & Fielden, 2014), and the Flying Start program for nurses within the National Health Service (NHS) in the United Kingdom (Solowiej, Upton, & Upton, 2010), all serve as formal mentoring programs that target the specific needs of those individuals within the profession.…”
Section: Types Of Mentoringmentioning
confidence: 99%
“…Woolnough and Fielden (2014) examined the impact of implementing a career development and mentoring program for female nurses working in the mental health sector. The authors found that those that had access to the formal mentorship program had significantly higher rates of promotion within their jobs, had an increase in self-confidence and self-esteem, reported a perceived increase in leadership effectiveness, and were able to highlight multiple examples of personal growth and development based on the techniques they had learned (Woolnough & Fielden, 2014). Additionally, Solowiej, Upton & Upton (2010) found that newly qualified practitioners enrolled in the Flying Start program had an increase in self-value as a practitioner, and the program was beneficial to their career development.…”
Section: Types Of Mentoringmentioning
confidence: 99%
See 3 more Smart Citations